The orientation of the standard six pupil transferring from primary to secondary schooling - Pollock, Graeme Mackenzie (Rhodes University, Faculty of Education, Department of Education, 1988)
Pupils entering High School for the first time experience many problems of orientation and adjustment. This study arose from the conviction that something could be done to alleviate this time of stress to the benefit of both pupil and school alike. A brief review of literature showed that despite a fair amount of research having been done in Britain and the United States, there is still a dearth of information relating directly to the South African situation. Most transition studies differentiate between factors affecting academic adjustment, those relating to personal adjustment after transfer, and those which involve adjustment to environmental factors. In general studies approached orientation pogrammes from two perspectives - those that handled orientation as an event with its concomitant administrative and practical advantages, and those that saw it to be a process which has more person-focussed advantages. Most researchers agree that each school has its own needs and that the orientation programme should reflect those needs. Many favour a problem-solving approach to the design of any programme and emphasize the need for constant evaluation of the programme to maintain relevance and effectiveness. A low-key investigation into adjustment problems faced by new pupils in the High School was conducted by means of a questionnaire. Three main areas of information were investigated: attitude to school; personal adjustment as indicated by the self-concept; and general impression of Secondary School. The results confirmed that problems of orientation and adjustment are experienced by pupils in the South African Education System and revealed a framework upon which an orientation programme could be based. An overview of existing orientation programme objectives stresses the fact that orientation must be concerned with the total adjustment of the child - personal, academic and environmental - and that, of necessity, it involves the whole family. An orientation programme is outlined and expanded upon in order to provide a framework upon which other programmes could be designed, specific to the particular needs of the schools involved. Finally, certain observations are offered which may lead to a better understanding of the demands of the orientation process
Keywords: Student adjustment; Students, Transfer of